Antimicrobial Peptides and Human Disease - Shafer, William.; Shafer, William. (Current Topics in Microbiology and Immunology,, 2006)
Microbes are in our midst soon after birth. Thankfully, the number of harmless (and often beneficial) microbes far outnumber those that would do us harm. Our ability to ward-off pathogens in our environment, including those that can colonize our exterior and/or interior surfaces, depends on the integrative action of the innate and adaptive immunity systems. This volume of CTMI, entitled Antimicrobial Peptides and Human Disease, is dedicated to the role of antimicrobial peptides (AMPs) in the innate host defense system of homo sapiens.